2016
DOI: 10.1161/circresaha.115.308166
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-181b Improves Glucose Homeostasis and Insulin Sensitivity by Regulating Endothelial Function in White Adipose Tissue

Abstract: Rationale The pathogenesis of insulin resistance involves dysregulated gene expression and function in multiple cell types including endothelial cells (ECs). Posttranscriptional mechanisms such as microRNA-mediated regulation of gene expression could affect insulin action by modulating EC function. Objective To determine whether microRNA-181b (miR-181b) affects the pathogenesis of insulin resistance by regulating EC function in white adipose tissue during obesity. Methods and Results MiR-181b expression wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
101
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(105 citation statements)
references
References 76 publications
3
101
0
1
Order By: Relevance
“…However, enrichment in genes associated with M2 polarization was detected in HF-fed FoxO D compared to FoxO L/L muscles, suggesting that M2 polarization underlies the inhibition of inflammation. This shift in macrophage phenotype may occur as a consequence of FoxO-dependent changes in endothelial cell behavior, similar to the recent report that prevention of endothelial cell dysfunction promoted an M2 phenotype within local tissue-resident macrophages (35).…”
Section: Discussionsupporting
confidence: 89%
“…However, enrichment in genes associated with M2 polarization was detected in HF-fed FoxO D compared to FoxO L/L muscles, suggesting that M2 polarization underlies the inhibition of inflammation. This shift in macrophage phenotype may occur as a consequence of FoxO-dependent changes in endothelial cell behavior, similar to the recent report that prevention of endothelial cell dysfunction promoted an M2 phenotype within local tissue-resident macrophages (35).…”
Section: Discussionsupporting
confidence: 89%
“…Sun et al 19 also observed a reduction in macrophage infiltration into adipose tissue and a preferential polarization of adipose tissue macrophages to an M2 subtype in mice treated with miR-181b. While the reduced macrophage infiltration may be directly related to lower EC activation, it was not clear how altered EC activation could influence the polarization of infiltrated and resident macrophages in the adipose tissue.…”
mentioning
confidence: 91%
“…In summary, the study by Sun et al 19 demonstrated that miR-181b expression decreases early in a diet-induced obesity animal model. This reduction results in increased PHLPP2 expression, EC activation and immune cell infiltration, as well as decreased Akt phosphorylation.…”
mentioning
confidence: 92%
See 2 more Smart Citations